2014
DOI: 10.1089/cap.2014.0005
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Suicide-Related Behavior or Ideation in Child, Adolescent, and Adult Patients Treated with Atomoxetine

Abstract: http://www.clinicaltrials.gov . The data reported are from an analysis of 23 pediatric and 9 adult clinical trials completed between 1998 and 2011. Ten pediatric (Studies HFBD, HFBK, LYAC, LYAS, LYAT, LYAW, LYAX, LYBG, LYBI, and LYBP) and two adult trials (Studies LYAA and LYAO) were conducted before the requirement to post trials at initiation (ongoing as of July 1, 2005) and, therefore, do not have a registration number. The registration numbers for the 13 pediatric trials meeting this requirement are: NCT00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 57 publications
5
34
0
1
Order By: Relevance
“…As in the meta-analysis reported in 2008 by Bangs et al [29], no completed suicides were reported in the more recent and larger meta-analysis by Bangs et al [26], which involved 3883 pediatric patients from 23 double-blind, placebo-controlled clinical trials with short treatment durations (5-15 weeks). One (0.04 %) of 2445 atomoxetine-treated patients and none of 1438 placebo-treated patients were classified as showing suicidal behavior (MHRR = 1.19, p = 0.91) [26].…”
Section: Findings In the Predefined Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…As in the meta-analysis reported in 2008 by Bangs et al [29], no completed suicides were reported in the more recent and larger meta-analysis by Bangs et al [26], which involved 3883 pediatric patients from 23 double-blind, placebo-controlled clinical trials with short treatment durations (5-15 weeks). One (0.04 %) of 2445 atomoxetine-treated patients and none of 1438 placebo-treated patients were classified as showing suicidal behavior (MHRR = 1.19, p = 0.91) [26].…”
Section: Findings In the Predefined Literature Searchmentioning
confidence: 99%
“…In our predefined literature search, we identified 13 studies and two case reports related to suicidality or self-harm [17,18,[25][26][27][28][29][30][31][32][33][34][35][36][37]. The nine studies with the largest atomoxetine-treated patient populations (range 421-6818) were four meta-analyses and one pooled analysis of data from atomoxetine pediatric clinical trials, two national register-based studies, and two clinical trials [17, 25-27, 29, 30, 32, 33, 36].…”
Section: Findings In the Predefined Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional meta-analyses were published that were likewise compromised by sample size, resulting in limited inferences for rare events. 8,9 Also, there is some evidence of increased rates of suicide in nontrial populations. 10 In summary, available evidence lacks inferences for nonclinical trial populations, older adolescents, risk after 3 months of treatment, and, importantly, whether suicidal ideation indeed manifests in risk of suicide.…”
mentioning
confidence: 99%